Issues in intimate violence - Bergen, Raquel Kennedy (Sage Publications, 2010)
Section I. Child abuse --The youngest victims : violence toward children /Richard J. Gelles --Women and children at risk : a feminist perspective in child abuse /Evan Stark and Anne Flitcraft --Section II. Incest --Sexual victimization of children : incest and child sexual abuse /Kathleen Kendall-Tackett and Roberta Marshall --The making of a whore /Diana E.H. Russell --Section III. Violence in dating relationships --Male peer support and woman abuse in postsecondary school courtship : suggestins for new directions in sociological research /Walter S. DeKeseredy and Martin D. Schwartz --Violent men or violent women? Whose definition counts? /Dawn H. Currie --Section IV. Violence in gay and lesbian relationships --Violence and abuse in lesbian relatinships : theoretical and empirical issues /Claire M. Renzetti --Understanding domestic violence among gay and bisexual men /Gregory S. Merrill --Section V. Acquaintance rape --Facing the facts : date and acquaintance rape are significant problems for women /Mary P. Koss and Sarah L. Cook --Fraternities and rape on campus /Patircia Yancey Martin and Robert A. Hummer --Arrest and conviction rates for athletes accused of sexual assault /Jeffrey Benedict and Alan Klein --Section VI. Wife abuse --Why do men batter their wives? /James Ptacek --Old problems and new directions in the study of violence against women /Demie Kurz --Women's realities : defining violence against women by immigration, race, and class /Shamita Das Dasgupta --Section VII. Wife rape --Marital rape /Patricia Peacock --The reality of wife rape : women's experiences of sexual violence in marriage /Raquel Kennedy Bergen --Section VIII. Elder abuse --Violence and violent feelings : what causes them among family caregivers? /Karl Pillemer and J. Jill Suitor --Abuse of African American elders /Linner Ward Griffin, Oliver J. Williams, Joyce G. Reed.